Resolution of inflammation: an integrated view - Ortega-Gómez, Almudena (WILEY-VCH Verlag, 2013)
Resolution of inflammation is a coordinated and active process aimed at restoration of tissue integrity and function. This review integrates the key molecular and cellular mechanisms of resolution. We describe how abrogation of chemokine signalling blocks continued neutrophil tissue infiltration and how apoptotic neutrophils attract monocytes and macrophages to induce their clearance. Uptake of apoptotic neutrophils by macrophages reprograms macrophages towards a resolving phenotype, a key event to restore tissue homeostasis. Finally, we highlight the therapeutic potential that derives from understanding the mechanisms of resolution.